Diary of a wimpy kid hard luck - Kinney, Jeff (New York Amulet Books, 2013)
While trying to find a new best friend after feuding with Rowley, middle-school slacker Greg Heffley is warned by older family members that adolescence is a time to act more responsibly and to think seriously about his future.
Keywords: Maturation (Psychology) -- Fiction; Families -- Fiction; Friendship -- Fiction; Diaries -- Fiction; Humorous stories